Polarization-independent dual-band quasi-bound states in the continuum based on graphene metasurface for tunable THz sensing application - Liyu Zhang; Hanxin Shen; Zhong Huang (Scientific Reports)
Abstract To catch high quality (Q) factors is always pursued for optical resonators. In this study, polarization-independent dual-band quasi-bound states in the continuum (quasi-BIC) in a graphene-based metasurface is proposed for the first time in the terahertz regime. The quasi-BIC resonance modes with a Q factor of 176 is achieved by introducing symmetry breaking into the unit structure. The proposed metasurface is well analyzed, and both the numerical calculations and the coupled mode theory shows the Q-factors of dual quasi-BICs follow the inverse square dependence on the asymmetric parameter. To better understand the excitation mechanism of the quasi-BICs, we investigate the electric field distribution and surface current distribution. Notably, the quasi-BIC transmission spectra can be tuned up to 2.3 THz by varying the graphene’s chemical potential, while keeping the modulation depth of the transmission larger than 50%. For the application, we further demonstrate biosensors with maximum sensitivity of 6.75 THz/RIU and minimum of the limit of detection of 0.0214 RIU. Unlike polarization-sensitive graphene quasi-BIC biosensors limited by complex alignment correction process with the light source, our proposed metasurface can maintain good quasi-BIC characteristics for arbitrarily polarized incident light and various angles of incidences ranging from 0 to 65°, which will greatly enhance the robustness of biosensors to rival the refractive index detection capabilities.